Aḥsanulintiḵẖāb fi ẕikr-i maʻīshat-i Sayyidnā Abī Tarāb - Ḥaidar, Shāh Muḥammad ʻAlī (Ma̤tbaʻ-yi Ṣubḥ, 1933)
Biography of ʻAlī ibn Abī Tālib, ca. 600-661, 1st Imamam (Shiites) and 4th Caliph of Islam.